(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
Indonesia has a wealth of natural resources and a strategic position on the world energy map, making the energy sector in Indonesia very interesting to research. There are also research gaps or differences in research results, differences in variables, and research samples so that they are more interesting to research. The purpose of this study is to see how financial and macroeconomic performance affect stock prices with CSR as moderation in energy sector companies included in the ISSI index in 2020-2023. This study took 33 samples of companies from a total population of 66. The method used is quantitative using the eviews tool. Hypothesis testing uses the panel data method to look at partial influences and MRA to look at the role of moderation. The results of the study show that partially the liquidity ratio has no effect on the stock price, the profitability ratio has a positive influence on the stock price, the solvency ratio has a negative influence on the stock price, the market share has no influence on stock price, and macroeconomic variables have a negative influence on stock prices. Moderation has the result that CSR cannot moderate liquidity and profitability ratios, while solvency, market ratio, and macroeconomic ratios can be moderated.